Exercise Effects on Chemotherapy-Induced Peripheral Neuropathy: A Comprehensive Integrative Review. Issue 3 (May 2020) - Kanzawa-Lee, Grace A.; Larson, Janet L.; Resnicow, Kenneth; Smith, Ellen Marie Lavoie
Abstract : Background: No effective cures for chemotherapy-induced peripheral neuropathy (CIPN) are known; however, exercise may be beneficial. Objective: The purpose of this review was to synthesize high-quality research publications reporting the effects of exercise on CIPN and related outcomes among people of all age groups who received neurotoxic chemotherapy. Methods: PubMed, CINAHL, Scopus, PsycINFO, and SPORTDiscus databases were searched first between May and November 2016 and then again in April 2019 for all clinical trials and meta-analyses. Subsequent hand-searching continued through April 2019. Potential scientific bias was rigorously evaluated, using the CONSORT (Consolidated Standards of Reporting Trials) guidelines. Results: Thirteen studies (7 randomized controlled trials, 6 quasi-experiments) were found that reported exercise effects in various adult CIPN populations (ie, mixed cancer types and stages, chemotherapy regimens and status, and CIPN presence and severity). No studies provided high-quality evidence; 2 studies provided moderate-quality evidence. Most studies (76.3%) evaluated combined aerobic, strength, and balance training interventions of varying dosages. The most commonly improved outcomes were CIPN, balance, and fitness. All 7 studies with an aerobic exercise component led to significant—most studies showing moderate to large—CIPN benefits. Conclusions: Few studies—none of high quality or in child/adolescent populations—have evaluated exercise effects on CIPN. The exercise interventions, dosages, and settings have been too heterogeneous to identify the most beneficial intervention for other CIPN-related outcomes. However, aerobic exercise may be a key component of exercise interventions for CIPN. Implications for Practice: Although promising, the empirical evidence is insufficient to definitively conclude that exercise interventions ameliorate CIPN.